The portrayal of Zimbabwe’s presidential candidates in front page mainstream print media in the run up to the 2018 general elections - post Mugabe era : a case study of The Herald and Daily News - Shumba, Ellison Elliot (My University, 2021)
This study takes into cognisance Zimbabwe’s political history and how mainstream media has performed in the coverage of past elections. The 2018 election provided a new Post-Mugabe political terrain and therefore enabled how the media portrayed the highest number of candidates running for the Zimbabwean presidency in history. The plebiscite also saw the emergence of“ new” political figures in both the incumbent Emmerson Mnangagwa and the leading opposition candidate in Nelson Chamisa of the Movement Democratic Change-Alliance (MDC-A) party. This study is informed by past political transitions in other African countries and how the Zimbabwean transition shared similarities and differences to others on the continent. Using the mixed methods approach the study reveals how even in a Post-Mugabe era the mainstream print media remains polarised. The Herald bias towards the incumbent provided a veiled attempt to multiplicity coverage of other candidates. The less relevant candidates received front page coverage in the state-owned power marginalising the popular opposition candidate. Daily News remained biased towards the leading opposition candidate while gravitating towards the incumbent through advertising and coverage. This study highlights the need for a global south framework on comparative media studies in Africa
A research project submitted to the Faculty of Humanities, University of the Witwatersrand, Johannesburg, in partial fulfilment for the requirements for the degree of Master of Arts in Media Studies, 2021
Keywords: Presidential candidates-Zimbabwe; Zimbabwe-Politics and government